Molecular characterization and phylogenetic relatedness of dog-derived Rabies Viruses circulating in Cameroon between 2010 and 2016. - Serge Alain Sadeuh-Mba; Jean Blaise Momo; Laura Besong; Sévérin Loul; Richard Njouom (Public Library of Science (PLoS), 2017)
Rabies is enzootic among dog populations in some parts of Cameroon and the risk of human rabies is thought to be steadily high in these regions. However, the molecular epidemiology of circulating Rabies Virus (RABV) has been hardly considered in Cameroon as well as in most neighboring central African countries. To address this fundamental gap, 76 nucleoprotein (N) gene sequences of dog-derived RABV were obtained from 100 brain specimens sampled in Cameroon from 2010 to 2016. Studied sequences were subjected to molecular and phylogenetic analyses with reference strains retrieved from databases. The 71 studied Africa-1 isolates displayed 93.5-100% nucleotide (nt) and 98.3-100% amino-acid (aa) identities to each other while, the 5 studied Africa-2 isolates shared 99.4-99.7% sequence similarities at nt and aa levels. Maximum Likelihood based phylogenies inferred from nucleotide sequences confirmed all studied RABV isolates as members of the dog-related species 1 of the Lyssavirus genus. Individual isolates could be unambiguously assigned as either the Africa-1 subclade of the Cosmopolitan clade or the Africa 2 clade. The Africa-1 subclade appeared to be more prevalent and diversified. Indeed, 70 studied isolates segregated into 3 distinct circulating variants within Africa-1a lineage while a unique isolate was strikingly related to the Africa-1b lineage known to be prevalent in the neighboring Central African Republic and eastern Africa. Interestingly, all five Africa-2 isolates fell into the group-E lineage even though they appeared to be loosely related to databases available reference RABV; including those previously documented in Cameroon. This study uncovered the co-circulation of several Africa-1 and Africa-2 lineages in the southern regions of Cameroon. Striking phylogenetic outcasts to the geographic differentiation of RABV variants indicated that importation from close regions or neighboring countries apparently contributes to the sustainment of the enzootic cycle of domestic rabies in Cameroon.